FEATURES OF ENGLISH NEWSPAPER HEADLINES AND THE USE OF COLLOCATIONS WITH A VERB COMPONENT (Scientific journal of the Fergana State University, 2025)
This article provides detailed information on the structure, format, and literary language of English newspaper headlines. It then discusses lexical collocations with verb components and their use in headlines. Various headlines from well-known English newspapers are selected and subjected to functional-semantic and stylistic analysis. Based on the obtained results, the article identifies which types of verb component collocations are prevalent in official newspaper texts and explores the distinctive features of English newspaper headlines.